Praktik Kebijakan Pendidikan Islam Indonesia dari Era Pra Kolonial hingga Kurikulum 2013 - Afiq Fikri Almas (Ta'allum: Jurnal Pendidikan Islam, 2018)
This article is intended to reveal the basic theory of educational policy. The practice of Islamic education in Indonesia from its development to its policy implementation has also become a basic study of this article. This research includes literature research using laws, books, articles, and journals related to the Indonesian Islamic education policy and its implementation from the pre-colonial era to the Curriculum 2013 as a source of data. A theoretical study approach to a policy using an existing phenomena. The results of this study is indicating that the policy of Indonesian Islamic education has experienced a significant development in every era, although the implementation of the policy there are still many problems in several lines. The development and change of Islamic education policies have a positive impact every year, so that Indonesian Islamic education is more global and comprehensive and felt by all Indonesian citizens. Indonesian Islamic education has been developing every time until the curriculum 2013 with additional hours of lessons, but this great policy should need to be evaluated and accompanied by the development of professional educator resources. Because the development of material policies must be supported by human resources to advance the Indonesian Islamic education.